PENGARUH LIKUIDITAS DAN PROFITABILITAS TERHADAP HARGA SAHAM PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI DASAR DAN KIMIA SUB SEKTOR KIMIA YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Elsa Erianti; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The development of the business world makes many companies competing in the stock market. Through the capital market the company can raise funds to conduct economic activities because the capital derived from the owner of the company is usually not enough to run the company's operations. In the stock market of securities in the form of stocks become a special attraction for investors, where the stock can provide greater profits but, also can give big losses. The purpose of this study is to test the partial and simultaneous influence of liquidity and profitability to stock prices of chemical sub-companies. By using purposive sampling determined 7 companies as sample. This study uses secondary data from the company's financial statements. Analysis technique used is classical assumption test, multiple linear regression analysis. The results showed that partially (t test) liquidity and profitability did not affect the stock price. Based on F test liquidity and profitability does not affect the stock price of chemical sub-companies listed on the Indonesia Stock Exchange. Keywords: Liquidity, Profitability and Stock Price